Pretherapeutic PSMA PET-Derived Semiquantitative Parameters as Predictors of PSA Response in Patients with mCRPC Receiving [177Lu]Lu-PSMA-617 Radioligand Therapy - Dheeratama Siripongsatian; Attapon Jantarato; Chetsadaporn Promteangtrong; Anchisa Kunawudhi; Peerapon Kiatkittikul; Natphimol Boonkawin; Sukanya Yaset; Sirinsuda Somboon; Chanisa Chotipanich (Indian Journal of Radiology and Imaging, 2024)
Objective [177Lu]Lu-prostate-specific membrane antigen (PSMA)-617 radioligand therapy (RLT) shows promise for metastatic castration-resistant prostate cancer (mCRPC) patients with positive PSMA positron emission tomography (PET) imaging. Identifying high-risk patients is crucial. We evaluated pretherapeutic PSMA PET-derived parameters to predict prostate-specific antigen (PSA) response in patients undergoing [177Lu]Lu-PSMA-617 RLT.